The biochemical effects of carotenoids in orange carrots on the colonic proteome in a mouse model of diet-induced obesity - Balbuena, Emilio; Milhem, Fadia; Kiremitci, Buse Zeren; Williams, Taufika Islam; Collins, Leonard; Shu, Qingbo; Eroglu, Abdulkerim (Frontiers in Nutrition, 2024)
Carotenoids are naturally occurring pigments in plants and are responsible for the orange, yellow, and red color of fruits and vegetables. Carrots are one of the primary dietary sources of carotenoids.The biological activities of carotenoids in higher organisms, including their immunomodulatory activities, are well documented in most tissues but not the large intestine. The gastrointestinal barrier acts as a line of defense against the systemic invasion of pathogenic bacteria, especially at the colonic level. To test whether carotenoids in orange carrots can alleviate obesity-associated gut inflammation and strengthen the intestinal barrier function, male C57BL/6J mice were randomized to one of four experimental diets for 20 weeks (n = 20 animals/group): Low-fat diet (LFD, 10% calories from fat), high-fat diet (HFD, 45% calories from fat), HFD with white carrot powder (HFD + WC), or HFD with orange carrot powder (HFD + OC). Colon tissues were harvested to analyze the biochemical effects of carotenoids in carrots. The distal sections were subjected to isobaric labeling-based quantitative proteomics in which tryptic peptides were labeled with tandem mass tags, followed by fractionation and LC-MS/MS analysis in an Orbitrap Eclipse Tribrid instrument. High-performance liquid chromatography results revealed that the HFD+WC pellets were carotenoid-deficient, and the HFD+OC pellets contained high concentrations of provitamin A carotenoids, specifically α-carotene and β-carotene. As a result of the quantitative proteomics, a total of 4410 differentially expressed proteins were identified. Intestinal barrierassociated proteins were highly upregulated in the HFD+OC group, particularly mucin-2 (MUC-2). Upon closer investigation into mucosal activity, other proteins related to MUC-2 functionality and tight junction management were upregulated by the HFD+OC dietary intervention.Collectively, our findings suggest that carotenoid-rich foods can prevent high-fat diet-induced intestinal barrier disruption by promoting colonic mucus synthesis and secretion in mammalian organisms. Data are available via ProteomeXchange with identifier PXD054150.